Development of an efficient parentage assignment methodology for selective breeding of the octoploid Siberian sturgeon Acipenser baeri - Vandeputte, Marc; Chantry-Darmon, Céline; Mahla, Rachid; Haffray, Pierrick; Guyomard, René (HAL CCSD, 2013)
absent